THE INFLUENCE BRAND IMAGE, PROMOTION, AND PRODUCT QUALITY INFLUENCE ON CUSTOMER SATISFACTION ON J.CO DONUTS IN THE CITY OF LHOKSEUMAWE - Mulyanur Mulyanur; Heriyana Heriyana; Hamdiah Hamdiah; Rahmaniar Rahmaniar (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to determine the effect of brand image, promotion, and product quality on customer satisfaction of J.CO donuts in Lhokseumawe City. The data used in this study is primary data. The population in this study consists of all consumers or customers of J.CO in Lhokseumawe, with a sample of 105 respondents selected using non-probability sampling. The method used is a quantitative approach by collecting data through questionnaires distributed to J.CO customers in Lhokseumawe. The data analysis technique used is linear regression. The results indicate that partially and simultaneously, all three independent variables have a positive and significant effect on customer satisfaction. These findings suggest that in the food and beverage industry, marketing strategies that integrate attractive brand image, effective promotions, and good product quality are key factors in increasing customer satisfaction and loyalty.